Cross-modal representations of first-hand and vicarious pain, disgust and fairness in insular and cingulate cortex - Corrado Corradi-Dell’Acqua (Nature Portfolio, 2016)
Anterior insula (AI) and medial anterior cingulate cortex (mACC) are activated by self and vicarious pain, disgust and fairness, yet the overlap of these representations are not known. Here the authors provide evidence for shared neural codes in the left AI and mACC and distinct codes in the right AI.